Designing an Educational Environment in Six Steps: Teaching for Understanding and the Motivation for Understanding - Harpaz, Yoram (International Journal for Talent Development and Creativity)

(untitled) (International Centre for Innovation in Education/Lost Prizes International, 2021)
The first part of this article describes in brief the Six Steps methodology for designing educational environments—be they K-12 schools, tertiary institutions, community centers, youth movements, or the like—as set forth in my book Educational Design in Six Steps: A Strategic and Practical Scaffold (Routledge 2020). The second part of the article illustrates application of the Six Steps method in designing an educational environment the aims of which are teaching for understanding and the motivation for understanding.